Pengaruh Persepsi Kualitas Dan Promosi Terhadap Kepuasan Pelanggan Serta Dampaknya Pada Loyalitas Pelanggan Donat XYZ Cabang Mal Kelapa Gading - Riza Meilani; Triyono Arief Wahyudi (Research and Community Service UNIVERSITAS KALBIS, 2025)
This study examines the influence of perceived quality and promotion on customer satisfaction and its subsequent impact on customer loyalty at Donat XYZ, Kelapa Gading Mall Branch. The research employed a quantitative approach using both primary and secondary data sources. Data were collected from 250 respondents who had purchased and consumed Donat XYZ products. Statistical analysis was conducted using SPSS version 21. The findings reveal that perceived quality has a significant and positive effect on customer satisfaction, indicating that customers who perceive the products as high quality tend to be more satisfied. Similarly, promotional activities were found to have a significant and positive influence on customer satisfaction, suggesting that effective promotions contribute to a better customer experience. Furthermore, customer satisfaction significantly and positively affects customer loyalty. These results demonstrate that improving product quality perceptions and implementing attractive promotional strategies can enhance customer satisfaction, which in turn strengthens customer loyalty toward Donat XYZ.